Occurrence of Cognitive and Neurological Symptoms in Norwegian Dentists - Bjørn Hilt; Kristin Svendsen; Tore Syversen; Oddfrid Aas; Torgunn Qvenild (Elsevier, 2011)
Objectives: Previous investigations have presented some evidence of late cognitive effects in dental personnel exposed to metallic mercury. We wanted to examine if Norwegian dentists have an increased prevalence of symptoms consistent with neurological and/or cognitive malfunction. Methods: The study group consisted of 406 dentists from central Norway and 217 controls from the general population, all under the age of 70. They had responded to a standardised postal questionnaire (Euroquest) inquiring about seven symptoms in regard to neurology, psychosomatics, memory, concentration, mood, sleep disturbances, and fatigue. A score was calculated for each symptom based on 4 to 15 single questions scored on a scale from 1 (seldom or never) to 4 (very often). Results: The dentists and controls had a participation rate of 57.2 % and 42.9 % respectively. The dentists reported no more cognitive symptoms than the controls, with low average symptom scores from 1.16 for neurological symptoms in males to 1.73 for fatigue in females. Corresponding figures for the controls were 1.22 and 1.77. There were a total of 1.2 % of the dentists and 1.8 % of the controls who reported having three or more of the seven symptoms "often" or more frequently. Conclusion: Norwegian dentists do not report more cognitive and neurological symptoms than controls from the general population.